2018
DOI: 10.1124/dmd.117.080176
|View full text |Cite|
|
Sign up to set email alerts
|

Structure-Activity Relationships of the Main Bioactive Constituents of Euodia rutaecarpa on Aryl Hydrocarbon Receptor Activation and Associated Bile Acid Homeostasis

Abstract: Rutaecarpine (RUT), evodiamine (EOD), and dehydroevodiamine (DHED) are the three main bioactive indoloquinazoline alkaloids isolated from , a widely prescribed traditional Chinese medicine. Here, the structure-activity relationships of these analogs for aryl hydrocarbon receptor (AHR) activation were explored by use of-deficient () mice, primary hepatocyte cultures, luciferase reporter gene assays, in silico ligand-docking studies, and metabolomics. In vitro, both mRNA analysis of AHR target genes in mouse pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…Regarding the interaction of rutaecarpine with AhR, we provide both theoretical and experimental evidence demonstrating that rutaecarpine is a promising natural stimulant of mouse and human AhR. The results of molecular docking simulation showed that rutaecarpine was capable to interact with AhR, which is consistent with the molecular docking results of Zhang Y. et al (2018) . The binding mode of rutaecarpine is through interaction with residues outside the binding site instead of getting into the binding pocket of AhR.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Regarding the interaction of rutaecarpine with AhR, we provide both theoretical and experimental evidence demonstrating that rutaecarpine is a promising natural stimulant of mouse and human AhR. The results of molecular docking simulation showed that rutaecarpine was capable to interact with AhR, which is consistent with the molecular docking results of Zhang Y. et al (2018) . The binding mode of rutaecarpine is through interaction with residues outside the binding site instead of getting into the binding pocket of AhR.…”
Section: Discussionsupporting
confidence: 79%
“…Evodiamine, dehydroevodiamine, and rutaecarpine are three major bioactive components of Evodia rutaecarpine ( Zhang Y. et al, 2018 ; Zhang et al, 2020 ). Their effects on cardiovascular protection, hepatic lipid metabolism regulation, liver injury protection, degenerative neurological diseases improvement, and acute pancreatitis protection have been fully recorded ( Yan et al, 2018 ; Tian et al, 2019 ; Li et al, 2020 ; Zhao B. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies related to these four herbs have been conducted in our previous researches, including studies of the chemical composition [11], pharmacokinetics (PK) [12], pharmacology [13], and clinical application [14]. It is worth to mention that the systematic phytochemical investigations of the main constituents of PC, MF, and ER were clarified.…”
Section: Introductionmentioning
confidence: 99%
“…from Beijing John Long Technology Development (Beijing, China) and Chengdu Push Biotechnology (Chengdu, China), respectively. (-)-Licarin-B (2) [30], isopsoralen (8), psoralen (9), psoralidin (1), lespecyrtin B1 (3), isobavachromene (4), isobavachalcone (5), psorachalcone A (6), bavachin (7), neobavaisoflavone (15) [18,20,21,[31][32][33], 10-methoxywuchuyuamide I (10), dehydroevodiamine (11), wuchuyuamide-I (12), wuchuyuamide-III (14), evodiame (16), rutaecarpine (19), evocarpine (23), 1-methyl-2-decyl-4(1H)-quinolone (26) [34][35][36] were isolated from PC, MF, EF in our laboratory with the purity ≥98% which the structure identification were completed by 1 H-NMR, 13 C-NMR, and TOF-MS spectral analyses as described in our previous reports. Carbamazepine (Internal standard, IS, Cat No.…”
Section: Introductionmentioning
confidence: 99%